2016
DOI: 10.1371/journal.pone.0151702
|View full text |Cite
|
Sign up to set email alerts
|

Modeling HIV-1 Induced Neuroinflammation in Mice: Role of Platelets in Mediating Blood-Brain Barrier Dysfunction

Abstract: The number of HIV-1 positive individuals developing some form of HIV-associated neurocognitive disorder (HAND) is increasing. In these individuals, the integrity of the blood-brain barrier (BBB) is compromised due to an increase in exposure to pro-inflammatory mediators, viral proteins, and virus released from infected cells. It has been shown that soluble CD40L (sCD40L) is released upon platelet activation and is an important mediator of the pathogenesis of HAND but the underlying mechanisms are unclear, emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 112 publications
(143 reference statements)
4
52
2
Order By: Relevance
“…We further demonstrated that altered platelets have a remarkable ability to damage and cross the blood brain barrier [20]. This is not unexpected, since platelets are the source of multiple pro-inflammatory substances, including TNF, IL-6 and CD40, which are known for altering the BBB [18][19][20][21][22][23]. Besides their role in pathogenesis, platelets might also play a key role in the regulation of brain function.…”
Section: Platelets Role In the Central Nervous Systemmentioning
confidence: 87%
See 2 more Smart Citations
“…We further demonstrated that altered platelets have a remarkable ability to damage and cross the blood brain barrier [20]. This is not unexpected, since platelets are the source of multiple pro-inflammatory substances, including TNF, IL-6 and CD40, which are known for altering the BBB [18][19][20][21][22][23]. Besides their role in pathogenesis, platelets might also play a key role in the regulation of brain function.…”
Section: Platelets Role In the Central Nervous Systemmentioning
confidence: 87%
“…Yet the mechanisms of such a dysfunction are still under investigation [18][19][20][21][22][23]. Our group started by documenting the close relationship between thrombocytopenia, a condition characterized by low platelets, and cognitive alterations [19].…”
Section: Platelets Role In the Central Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, it appeared prudent to use species-specific substitutes for studies of innate and adaptive immunity. Thus, EcoHIV infection of conventional immunocompetent mice was used to address this question (Hadas et al , 2007; He et al , 2014; Jones et al , 2016; Potash et al , 2005). …”
Section: Discussionmentioning
confidence: 99%
“…EcoHIV infection mimics HIV and offers a testing paradigm for studies of virus-induced neurodegeneration (Hadas et al , 2007; He et al , 2014; Potash et al , 2005). Notably, EcoHIV enters and establishes an infection in the mouse brain as early as 3 weeks after viral exposure and can alter BBB permeability by 2 weeks (Jones et al , 2016). Infected brains express inflammatory factors and mediators such as C3a, IL-1B, STAT-1, and IL-6 indicating an active infection and anti-viral response (Potash et al , 2005).…”
Section: Discussionmentioning
confidence: 99%